An Analysis of Compound Words Usage on the @PopBase's X Account in 2024 - Alzahra, Aisah; Mei Hardiah; Elfrida; Iis Sujarwati; Ira Maisarah (UNIB Press, 2025)
This study aims to analyze the use of compound words on the @PopBase X account in 2024. Using a qualitative approach and the theory of Delahunty and Garvey (2010), this study focuses on identifying three types of compound words: endocentric, exocentric, and copulative. Data were collected from @PopBase tweets throughout 2024, specifically those related to entertainment news and pop culture. The findings of the study revealed that endocentric compounds dominated the data, with terms such as soundtrack and fanbase being the most frequently used. Exocentric compounds, such as box office and blockbuster, and copulative compounds, such as singer-songwriter and action comedy, also appeared but were less frequent. The study also found that most of the compounds had transparent meanings and the compounds in the posts functioned as nouns. These findings suggest that the use of compound words on @PopBase helps facilitate concise and engaging communication, especially in the fast-paced digital environment of platform X. This study contributes to the understanding of word formation in X application and highlights the evolving role of morphology in online entertainment communication.